Traditional Wisdom and Conservation of the Osing Tribal Community in Banyuwangi - Budi Prasetyo (Universitas Khairun, 2021)
In daily life, the interaction of the Osing people with their agricultural environment has resulted in various activities that have local wisdom values. All of these activities are still carried out in the midst of the rapid advancement of digital and online technology-based civilization. In addition, in their social life, the community is consistent in carrying out and preserving various traditional ritual traditions from their ancestral heritage. The research aims to make an inventory of various activities that have local wisdom values and record they carry out traditional conservation of the biological resources in their environment. The research used a qualitative descriptive method, while data collection was carried out through observation and interviews in Focus Group Discussions (FGD). The data analysis process uses cross-checking, summarizing, and synthesizing. The results showed that there were various activities of the Osing community that contained local wisdom values, including farming practices using the Javanese calendar (pranotomongso) and the history of making and placing garden lands that function as buffer areas for paddy fields to prevent landslides. ancestors of the Osing tribe. The division of tasks in farming activities in the rice fields carried out by men and women of the Osing tribe reflects a combination of activities that have aspects of local wisdom. Likewise, the use of straw as animal feed and natural organic fertilizers, as well as the use of a kettle, fishing tools, the use of hunting dogs to get wild animals, and skills in the process of making traditional tools. The Osing community carries out traditional ecosystem-based conservation to protect all plants that grow on their agricultural lands. In addition, in maintaining the sustainability of clean water springs (belik) along the banks of the Sobo and Gulung rivers, they do this by making a ban on cutting down trees that grow around the riverbanks and performing the rebo wekasan salvation ritual.